2022
DOI: 10.3390/ma15248867
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protonic Conductor SrLa2Sc2O7 with Layered Structure for Electrochemical Devices

Abstract: Novel materials with target properties for different electrochemical energy conversion and storage devices are currently being actively created and investigated. Materials with high level of protonic conductivity are attracting attention as electrolytes for solid oxide fuel cells and electrolyzers. Though many materials are being investigated as potential electrolytic components for these devices, many problems exist, including comparability between electrodes and electrolytes. In this paper, layered perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Currently, a large class of materials with the monolayer perovskite structure Ba(Sr)La(Nd)In(Sc)O4 [37][38][39][40][41] is described in terms of proton transport. The possibility of proton conductivity in bilayer AA′2B2O7 perovskites such as on BaLa2In2O7 [42][43][44], BaNd2In2O7 [45] and SrLa2Sc2O7 [46] and compositions based on them was described last year. It was shown that doping cationic sublattices can improve oxygen-ion and proton conductivity by up to 1.5 orders of magnitude [12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a large class of materials with the monolayer perovskite structure Ba(Sr)La(Nd)In(Sc)O4 [37][38][39][40][41] is described in terms of proton transport. The possibility of proton conductivity in bilayer AA′2B2O7 perovskites such as on BaLa2In2O7 [42][43][44], BaNd2In2O7 [45] and SrLa2Sc2O7 [46] and compositions based on them was described last year. It was shown that doping cationic sublattices can improve oxygen-ion and proton conductivity by up to 1.5 orders of magnitude [12].…”
Section: Introductionmentioning
confidence: 99%